FACTORS PREDICTING MORTALITY IN COVID-19 PATIENTS WITH CARDIOVASCULAR COMORBIDITY - SIREGAR, CINDY OKTAVIA; HANDAYANI, AHMAD (LP2MTBM MAKARIOZ, 2023)
The presence of rapidly spreading Corona virus or SARS-CoV-2 throughout the world became a public concern and maajor problem for the world’s population due to it’s high mortality rate.. The COVID-19 patients was often accompanied by the presence of underlying diseases which one of them is cardiovascular disease (CVDs) which tends to aggravate the symptoms and worsen the prognosis. It is necessary to evaluate some factors that make contributions of predicting the risks of death in this population. This was a retrospective analytical study with cross sectional design with total samples of 42 patients who were hospitalized in Mitra Medika Amplas General Hospital Medan. Several factors were identified and statistical analysis were done to analyze the relationship between them with the risk of mortality. This study found that several factors contributed to the risk of mortality in COVID-19 with CVDs which are male gender, lower oxygen saturation at admission, increased renal function laboratory values. Male gender, initial oxygen saturation, ureum and creatinine are factors predicting mortality in COVID-19 patients with cardiovascular comorbidity.